The therapeutic potential of natural medicine puerarin for depression - Guo, Yuchao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The incidence of depression has steadily increased in recent years, making it one of the most prevalent mental disorders. As the pursuit of new antidepressant drugs has attracted wide attention in the pharmaceutical community, the therapeutic effects of traditional Chinese medicine have also been extensively explored. Puerarin is commonly used as a vasodilator in the treatment of coronary heart disease including angina and myocardial ischemia, cerebral infarction, retinal vein occlusion, and sudden deafness. However, the potential of puerarin in the treatment of depression is very great, so this article reviews the latest research progress of puerarin in the mechanism of depression in recent years, and discusses its application prospect in depression. In addition, we also discuss the related pathological mechanism of depression, which provides new insights for further understanding of depression. However, despite the great potential of puerarin, further studies are needed to elucidate its specific mechanism of action and evaluate its effectiveness in human subjects.